Dynamics of Madrasah Principals' Managerial Practices in Managing Educational Personnel - Mawardi; Husni Hidayat; Madian Al Fikri (Journal of Educational Management Research, 2024)
This study aims to explore the dynamics of madrasah principals’ managerial practices in managing educational personnel. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis to capture managerial processes, leadership interactions, and personnel management practices in natural settings. The findings reveal that principals enact managerial practices dynamically through adaptive planning, flexible organization and coordination, context-sensitive supervision, and inclusive decision-making. These practices enable principals to respond effectively to organizational challenges, align personnel management with institutional goals, and foster a collaborative and supportive work environment. The study highlights that managerial effectiveness in madrasahs is not determined solely by technical competence, but by the ability to adapt leadership practices to contextual and human resource conditions. The implications of this study suggest that leadership development programs for madrasah principals should emphasize dynamic managerial capabilities, reflective supervision, and participatory decision-making. By advancing a dynamic perspective on managerial leadership, this research contributes to educational management scholarship and provides practical insights for improving personnel management in Islamic educational institutions.